The official United States Navy SEAL workout - Flach, Andrew (The official Five Star fitness guides., 1998)
The Official United States Navy SEAL Workout presents an accurate documentation of the demanding physical training (or P.T., as it's known in military circles) that students encounter at BUD/S. The physical expectations of BUD/S graduates are awesome...but they are achievable, as this book demonstrates.You'll learn what it's like to be a SEAL in this incredible book that brings together the fitness requirements, history, and traditions of the US Navy SEALs.